Historical Perspectives in Industrial and Organizational Psychology / Ed. - Bryan, Laura L. Koppes (New York : Routledge, 2021)
"Historical Perspectives in Industrial and Organizational Psychology, Second Edition updates the first edition with the latest creative and scholarly views of I-O psychology to provide a complete, up-to-date understanding of this discipline's history within a contemporary context. This new edition includes updated chapters from the first edition as well as three completely new chapters: a history of LGBTQ+ employees' workplace experiences, the evolution of worker well-being and work-life issues, and a reflection on the importance of context when studying workplaces and whether or not the science and practice of I-O psychology is prepared for the future. Historical Perspectives in Industrial and Organizational Psychology, Second Edition compiles chapters written from the historical perspectives of I-O psychologists, historians, and other experts in their fields, all of whom use historical analyses as the method of inquiry rather than provide summarized overviews of the topics. Chapter authors rely on archival materials, primary and secondary sources, as well as interviews with luminaries and experts. Historical Perspectives in Industrial and Organizational Psychology, Second Edition is essential reading for contemporary and aspiring scholars of I-O psychology and related fields, such as history of psychology, human resource management, organizational behavior, and public administration. Both scientists and practitioners will benefit from reading this text"--
Keywords: Psychology, Industrial -- History; Organizational behavior -- History